Characteristics and Correlation Between Progesterone Receptors and The Use of Hormonal Contraceptive in Women with Meningioma in dr. Cipto Mangunkusumo National General Hospital - Setyo Widi Nugroho; Harris Istianggoro; Fabianto Santoso; David Tandian; Renindra Ananda Aman; Eka Susanto (eJournal Kedokteran Indonesia, 2022)
Meningiomas are the most common primary, intracranial and extra axial tumours, estimated for 30% of all intracranial tumors. The use of hormonal contraceptive is one of the risk factors for meningioma, but the studies still have controversial results. The purpose of this study is to describe the characteristics and to correlate between progesterone receptor and the use of hormonal contraceptive in women diagnosed with brain tumor meningioma. This is a cross-sectional study which collect data in dr. Cipto Mangunkusumo National General Hospital in the year 2017-2018. Patient data collection was obtained through the patient’s medical records, whereas the subjects are women with brain tumors meningioma who have undergone surgery. We found 72 women diagnosed with meningioma; however, only 54 subjects were included in this study. Immunohistochemistry staining were performed to all the 54 subjects and revealed that 53 subjects (98.15%) had positive progesterone receptors and only 1 subject was negative (1.85%). Of the 53 subjects with positive progesterone receptors, 48 subjects used hormonal contraceptive (90.57%), with 43 (89.58%) of them used 3 month injectable contraceptive. There is no correlation between progesterone receptors and the use of hormonal contraceptives in female patients with meningioma brain tumor (p value >0.999, Fisher Test). Keywords: meningioma, hormonal contraception, progesterone receptor.   Karakteristik dan Korelasi antara Progesteron Reseptor dan Penggunaan Kontrasepsi Hormonal pada Perempuan dengan Meningioma di RSUPN Dr. Cipto Mangunkusumo Abstrak Meningioma adalah tumor intrakranial ekstraaksial primer terbanyak dengan perkiraan 30% dari seluruh tumor intrakranial. Penggunaan kontrasepsi hormonal diduga menjadi salah satu faktor risiko meningioma, namun hasil penelitian masih kontroversial. Tujuan penelitian ini adalah mengetahui karakteristik dan korelasi antara progesteron reseptor dan penggunaan kontrasepsi hormonal pada perempuan dengan meningioma. Studi potong lintang ini menggunakan data rekam medis RSUPN dr. Cipto Mangunkusumo pada tahun 2017-2018. Data pasien dikumpuikan melalui rekam medis dimana subyek adalah pasien meningioma intrakranial yang dilakukan operasi. Terdapat 72 perempuan yang didiagnosis meningioma, namun data yang dapat dianalisis adalah 54 subyek. Hasil pewarnaan imunohistokimia didapatkan 53 subyek (98,15%) memiliki reseptor progesteron positif. Dari kelompok reseptor progesteron yang positif, 48 subyek (90,57%) menggunakan kontrasepsi hormonal dengan mayoritas (89,58%) menggunakan kontrasepsi injeksi 3 bulan. Tidak didapatkan korelasi antara reseptor progesteron dengan penggunaan kontrasepsi hormonal pada perempuan dengan meningioma (nilai p >0,999, Uji Fisher). Kata kunci: meningioma, kontrasepsi hormonal, reseptor progesteron